Simulation of the scrapers with pusher - Nilov V.A. (Научно-технический вестник Брянского государственного университета)
The question of the economic-mathematical modeling of working process of trailed scraper working with a tractor-pusher. The modeling was done on computer taking into account the technical parameters of the tractor and the pusher, ground and road conditions, as well as the cost of the equipment, capital and replacement costs. The presence of a ra-tional capacity bucket scraper, providing the maximum output per shift and reduced unit development costs of 1 m3 of soil. The positive effect of the operation at the chain scrapers, wheel tractors and the need for dogugaeshi devices, in-creasing the coupling weight of the tractor wheel.